2013
DOI: 10.1103/physrevb.87.054107
|View full text |Cite
|
Sign up to set email alerts
|

Metallization of magnesium polyhydrides under pressure

Abstract: Evolutionary structure searches are used to predict stable phases with unique stoichiometries in the hydrogenrich region of the magnesium/hydrogen phase diagram under pressure. MgH4, MgH12 and MgH16 are found to be thermodynamically stable with respect to decomposition into MgH2 and H2 near 100 GPa, and all lie on the convex hull by 200 GPa. MgH4 contains two H − anions and one H2 molecule per Mg 2+ cation, whereas the hydrogenic sublattices of MgH12 and MgH16 are composed solely of H δ− 2 molecules. The high-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
140
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 65 publications
(87 reference statements)
5
140
2
Order By: Relevance
“…This structure was optimized with fully relaxing the atoms and lattice parameters within firstprinciples electronic structure framework, which produces a body centered cubic (bcc) crystal structure and space group of Im-3m with 14 atoms per unit cell, in agreement with our previous work. 1), where previously predicted P6 3 /mmc Ni 2 In-type structure 21 was used for MgH 2 and C2/c and Cmca-12 structure 22 were used for solid hydrogen. 1), where previously predicted P6 3 /mmc Ni 2 In-type structure 21 was used for MgH 2 and C2/c and Cmca-12 structure 22 were used for solid hydrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This structure was optimized with fully relaxing the atoms and lattice parameters within firstprinciples electronic structure framework, which produces a body centered cubic (bcc) crystal structure and space group of Im-3m with 14 atoms per unit cell, in agreement with our previous work. 1), where previously predicted P6 3 /mmc Ni 2 In-type structure 21 was used for MgH 2 and C2/c and Cmca-12 structure 22 were used for solid hydrogen. 1), where previously predicted P6 3 /mmc Ni 2 In-type structure 21 was used for MgH 2 and C2/c and Cmca-12 structure 22 were used for solid hydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] At present, the superconducting mechanism of compressed H 2 S is not quite clear and remains elusive. 21 In this work, we study the stability of MgH 6 relative to MgH 2 and H 2 on the basis of first-principle density functional theory. Recently, CaH 6 has been predicted to have a good superconductivity of 235 K at 150 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, building on Ashcroft's proposals, density functional theory (DFT) calculations were carried out to predict the structures of hydrides with stoichiometries that are not stable at atmospheric conditions, in the hopes of uncovering hitherto unknown superconductors [19]. Since then, numerous theoretical studies have been performed that investigate the phase diagrams of hydrogen doped with the electropositive alkali metals or alkaline earth metals [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], as well as the electronegative element iodine [35,36] under pressure. Experimental work on the hydrides of lithium and sodium confirmed that species with unique stoichiometries such as NaH 3 and NaH 7 can be synthesized in diamond anvil cells, but the phases that have been reported to date do not exhibit superconductivity [21,37].…”
Section: Introductionmentioning
confidence: 99%
“…New polyhydride phases are also anticipated for alkaline earth metals [24,72,73]. The theoretically predicted polyhydrides are not only stabilized by compression, but are expected to metalize and exhibit superconducting properties at lower pressures than the constituent parts -the monohydride and hydrogen.…”
Section: Polyhydrides Of Alkali and Alkaline Earth Metalsmentioning
confidence: 91%